2014
DOI: 10.1209/0295-5075/108/10005
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Dirac oscillator in a thermal bath

Abstract: The thermal properties of the three-dimensional Dirac oscillator are considered. The canonical partition function is determined, and the high-temperature limit is assessed. The degeneracy of energy levels and their physical implications on the main thermodynamic functions are analyzed, revealing that these functions assume values greater than the one-dimensional case. So that at high temperatures, the limit value of the specific heat is three times bigger.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 23 publications
(37 reference statements)
1
49
0
Order By: Relevance
“…To perform our analysis on the thermodynamics of the DKP oscillator, we will restrict ourselves to stationary states of positive energy. The reasons are as follows [31,38,39]. First, according to the study in [40,41], the DKP equation possesses an exact Foldy-Wouthuysen transformation (FWT): thus, the positive-and negative-energy levels never mix.…”
Section: Thermodynamic Properties Of the Dkp Oscillator For Spin 0 Pamentioning
confidence: 99%
See 1 more Smart Citation
“…To perform our analysis on the thermodynamics of the DKP oscillator, we will restrict ourselves to stationary states of positive energy. The reasons are as follows [31,38,39]. First, according to the study in [40,41], the DKP equation possesses an exact Foldy-Wouthuysen transformation (FWT): thus, the positive-and negative-energy levels never mix.…”
Section: Thermodynamic Properties Of the Dkp Oscillator For Spin 0 Pamentioning
confidence: 99%
“…The DKP equation in the presence of the Dirac oscillator interaction called DKP oscillator for spin zero and spin one particles has also been investigated in the NC formalism in publications [26][27][28], with the purpose of obtaining the energy spectrum and studying the noncommutative effect on relativistic quantum mechanics. In addition, the studies of thermal properties of the quantum oscillator have been 2 Advances in High Energy Physics carried out in both commutative and NC space by several authors these years [29][30][31][32][33][34]. By employing the numerical method based on the Euler-MacLaurin formula, one can calculate the associated partition function and obtain the thermodynamic functions, such as the free energy, mean energy, heat capacity, and entropy.…”
Section: Introductionmentioning
confidence: 99%
“…Pacheco et al considered one and three dimensional Dirac oscillators in a thermal bath and determined their canonical partition functions. Then, they analyzed the main thermodynamic functions and concluded that in higher values of temperature the specific heat functions are much greater [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interest to the thermodynamic functions, which play significant role to understand fully the physical properties of different potential fields in either relativistic or non-relativistic regimes, has been increased. Pacheco et al have analyzed one [1] and three dimensional [2] Dirac oscillator in a thermal bath. Boumali has studied relativistic harmonic oscillator in context of thermodynamics [3], calculated the thermal properties of graphene under a magnetic field via the two dimensional Dirac oscillator [4] and thermodynamic properties of the one-dimensional Duffin-Kemmer-Petiau oscillator by using the Hurwitz zeta function method [5].…”
Section: Introductionmentioning
confidence: 99%